Bài 8: Rút gọn biểu thức chứa căn bậc hai

NT
15 tháng 1 2023 lúc 21:20

1: Khi x=36 thì \(A=\dfrac{6+1}{36-3\cdot6}=\dfrac{7}{36-18}=\dfrac{7}{18}\)

2: \(=\dfrac{2x-6\sqrt{x}+x+3\sqrt{x}-3x-9}{x-9}=\dfrac{-3\left(\sqrt{x}+3\right)}{x-9}=-\dfrac{3}{\sqrt{x}-3}\)

3: \(P=B:A\)

\(=\dfrac{-3}{\sqrt{x}-3}:\dfrac{\sqrt{x}+1}{\sqrt{x}\left(\sqrt{x}-3\right)}=\dfrac{-3\sqrt{x}}{\sqrt{x}+1}\)

a: Để P<-1/2 thì P+1/2<0

\(\Leftrightarrow-\dfrac{3\sqrt{x}}{\sqrt{x}+1}+\dfrac{1}{2}< 0\)

=>\(-6\sqrt{x}+\sqrt{x}+1< 0\)

=>-5 căn x<-1

=>x>1/25

Bình luận (0)